Actual availability of general practice appointments for mildly ill children. Issue 3 (3rd August 2015) - Freed, Gary L; Bingham, Amie; Allen, Amy R; Freed, Michele; Sanci, Lena A; Spike, Neil
Abstract: Objective: To determine actual availability and cost of general practitioner appointments for children with conditions of low acuity and low urgency, from the perspective of the child's family. Design, participants and setting: A "secret shopper" method, whereby research assistants posing as parents seeking appointments for mildly ill children telephoned a random sample of 225 general practice clinics within three Melbourne Medicare Local catchments, which included urban, suburban and regional areas; the study was conducted between 1 August and 30 September 2014. Main outcome measures: Availability of same‐day appointments and time until appointment; bulk‐billing status of the clinic and/or the potential cost of an appointment. Results: High availability of appointments was found in all three catchment areas (range, 72%–81% of clinics contacted). About half (49%) had appointments available within 4 hours. Between 72% and 80% of clinics contacted in the three Medicare Local catchment areas offered bulk‐billing for paediatric appointments. Conclusion: There is extensive same‐day new‐patient GP appointment availability for mildly ill children in the catchment areas of Melbourne studied. Further, as most of the available appointments are in clinics that bulk bill, financial access should not affect this availability. Increased paediatric presentations to emergency departments are not likely to be the result of limited GP availability. These findings provide an important base for developing data‐driven policy approaches to the development and use of primary care.